Association between personality traits and experience of adverse periocular reactions to topical prostaglandin analogues. Issue 1 (24th June 2022) - Kishimoto, Nanami; Noro, Takahiko; Kodaka, Fumitoshi; Kurosawa, Mei; Itoh, Yoshinori; Ogawa, Shumpei; Watanabe, Tomoyuki; Kubota, Masaomi; Hori, Kiyotaka; Shigeta, Masahiro; Nakano, Tadashi
Abstract : Background: Aesthetically unappealing adverse periocular reactions to prostaglandin (PG) eye-drops are a major challenge in glaucoma treatment. This study analysed the personality traits of patients with glaucoma based on a five-factor model and examined the associations between these factors and adverse periocular reactions. Methods: One hundred and forty-seven patients with glaucoma were surveyed anonymously regarding their personality traits and how often adverse periocular reactions were experienced. Results: The analysis included 117 valid responses (71 men and 46 women, age: 61.9±11.5 years). Patients who experienced hypertrichosis of the eyelashes scored significantly higher on extraversion (p<0.05), with no significant differences in the other four personality traits. Patients who experienced eyelid hyperpigmentation and deepening of the upper eyelid sulcus showed no significant differences in any of the personality traits. Younger patients scored significantly higher on hypertrichosis (p<0.05). Conclusion: The experience of adverse reactions differed according to patient age and personality traits. Therefore, eye-drops should be chosen based on these factors. Trial registration number: UMIN000035155.